A study of word cooccurrence and drawing a scientific map of audiovisual sports media based on scientific articles indexed in Web of Science - Mohammad Eslamfar; Seyed Hossein Marashian; Amin Khatibi; Tahereh Azmsha (مجله علم‌سنجی کاسپین, 2024)
Background and aim: The main objective of the present study is to draw a scientific map of audiovisual sports media based on scientific articles indexed in the Web of Science database during the years 2016-2023.